Adsorption of ammonium-nitrogen from aqueous solution using chitosan-coated bentonite beads - Jurado, Climaco A.Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Excess ammonium-nitrogen (NH4-N) causes eutrophication, depletion of dissolved oxygen and eventual deterioration of water bodies. In this study, the removal of NH4-N from simulated wastewater using chitosan-coated bentonite (CCB) adsorbents was investigated. The effects of initial NH4-N concentration, solution pH, CCB dosage, agitation rate and solution temperature on NH4-N removal were determined. NH4-N removal increased with CCB dosage, agitation rate and temperature and decreased with initial NH4-N concentration. NH4-N removal of 67.5% was attained at pH 4, CCB dosage of 8 g, agitation rate of 150 rpm and solution temperature of 35 degree Celsius. Based on the results of the Fourier transform infrared (FTIR) analysis, NH4-N adsorption onto CCB involves the O-H and the anime functional groups. At solution temperature of 25 degree Celsius, experimental date follows the pseudo-second order kinetic model (R2 = 0.9964) and the Koble-Corrigan isotherm (R2 = 0.9704). Thermodynamic studies showed that the adsorption process is spontaneous (ΔG<0) and endothermic (ΔH>0) in nature. The results of this study demonstrated that CCB can be a potential adsorbent for the removal of NH4-N from aqueous solutions.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Sewage -- Environmental aspects; Sewage -- Purification -- Adsorption; Sewage -- Purification -- Nitrogen removal; Aqueous solutions